2020
DOI: 10.3389/fcell.2020.00771
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12-CXCR4 Interplay Facilitates Palatal Osteogenesis in Mice

Abstract: Cranial neural crest cells (CNCCs), identified by expression of transcription factor Sox9, migrate to the first branchial arch and undergo proliferation and differentiation to form the cartilage and bone structures of the orofacial region, including the palatal bone. Sox9 promotes osteogenic differentiation and stimulates CXCL12-CXCR4 chemokinereceptor signaling, which elevates alkaline phosphatase (ALP)-activity in osteoblasts to initiate bone mineralization. Disintegration of the midline epithelial seam (MES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 128 publications
(163 reference statements)
0
9
0
Order By: Relevance
“…There is little difference between chemokine interaction pairs in OBs, and they all express CXCR4 to promote OB proliferation and differentiation; however, only MinOBs do not secrete CXCL12. 27 At the end of osteogenic differentiation, CXCL12 is downregulated. 28 We found that the overall expression of the ephrin receptor and NOTCH family members decreased gradually from EnOBs to StOBs to MinOBs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little difference between chemokine interaction pairs in OBs, and they all express CXCR4 to promote OB proliferation and differentiation; however, only MinOBs do not secrete CXCL12. 27 At the end of osteogenic differentiation, CXCL12 is downregulated. 28 We found that the overall expression of the ephrin receptor and NOTCH family members decreased gradually from EnOBs to StOBs to MinOBs.…”
Section: Resultsmentioning
confidence: 99%
“…There is little difference between chemokine interaction pairs in OBs, and they all express CXCR4 to promote OB proliferation and differentiation; however, only MinOBs do not secrete CXCL12 27. At the end of osteogenic differentiation, CXCL12 is downregulated 28.…”
Section: Resultsmentioning
confidence: 99%
“…There is little difference between chemokine interaction pairs in OBs, and they all express CXCR4 to promote OB proliferation and differentiation, however, only MinOBs do not secrete CXCL12. 24 At the end of osteogenic differentiation, CXCL12 is downregulated. 25 We found that the overall expression of the ephrin receptor and NOTCH family members decreased gradually from EnOBs to StOBs to MinOBs.…”
Section: Vascular Ec and Ob Subpopulation Interactionmentioning
confidence: 99%
“…Although the first known activity of CXCR4 was the regulation of HIV- infection and cancer metastasis ( Bleul et al, 1997 ; Helbig et al, 2003 ; Doi et al, 2018 ; Shanmugam et al, 2018 ; Bianchi and Mezzapelle, 2020 ), CXCR4 is also an abundantly expressed chemokine receptor throughout embryogenesis ( Yusuf et al, 2005 ; Yusuf et al, 2006 ). The functions of the CXCR4/SDF-1 axis during embryogenesis include heart ventricular septum formation, gut vascular morphogenesis, sympathetic precursor cell migration, dentate granule cell migration, B lymphocyte migration, sensory neuron clustering, limb neuromuscular development and palatal osteogenesis ( Bagri et al, 2002 ; Odemis et al, 2005 ; Kasemeier-Kulesa et al, 2010 ; Escot et al, 2013 ; Mahadevan et al, 2014 ; Terheyden-Keighley et al, 2018 ; Laparidou et al, 2020 ; Verheijen et al, 2020 ; Yahya et al, 2020a ).…”
Section: Cell Migrationmentioning
confidence: 99%